(untitled) (Bangladesh Journal of Medicine, 2015)
Glomerulonephritis are categorised into several different pathological patterns, which are broadly grouped into non-proliferative or proliferative types.4 Glomerulonephritis comprises 25-45% cases of end-stage renal disease (ESRD) in developing nations, like Bangladesh.5 This study has been done in Dhaka Medical College Hospital from January 2011 to December 2011 to find out the type of glomerulonephritis among presented glomerulonephritis patients to Inpatient and Outpatient Department of Nephrology aiming to reflect the pattern of glomerulonephritis in Bangladeshi population. The current study duration was 12 months, 128 patients having glomerulonephritis were included in this study. Statistical analysis has been done using the stastical package for social science. In this current study it was observed that most (31.3%) of the patients were in the age group of 31 to 40 years and the mean±SD of age was 32.94±12.66 years ranging from 18 to 70 years. In this current study it was observed that 64.8% was male and 35.2% was female. Male female ratio was 1.8:1. According to type of glomerulonephtis evaluated by histopathology, it was observed that in Non Proliferative Glomerulonephtis: 12(10.61%) is Minimal Change Disease (MCD), 9(7.96%) is Focal Segmental Glomerulosclerosis (FSGS), 25(22.12%) is Membranous Glomerulonephritis (MGN). In Proliferative Glomerulonephtis: Membranoproliferative Glomerulonephtis- 13(11.5%), IgA Nephropathy -13(11.5%), Mesengial Proliferative Glomerulonephtis -14(12.39%), Focal Segmental Proliferative Glomerulonephtis-14(14.2%), Rapidly Progressive Glomerulonephtis (RPGN) - 2 (1.8%). and Chronic Sclerosing Glomerulonephritis is -11(9.7%). In our study to find out the pattern of Primary Glomerulonephritis in Dhaka Medical College Hospital there is almost similar findings in Bangladeshi and South Asian population which is shown in different studies in this region. We have some variation with Western, European, American, Middle East studies which is may be due to the difference in environmental, genetic, racial, social and economic variation. Bangladesh J Medicine Jul 2014; 25 (2) : 42-46